Carlsberg alibi marketing in the UEFA Euro 2016 football finals: implications of Probably inappropriate alcohol advertising - Murray, Rachel L.; Opazo-Breton, Magdalena; Britton, John; Cranwell, Joanne; Grant-Braham, Bruce (BioMed Central, 2018)
Background: Alcohol advertising is a key driver of alcohol consumption, and is prohibited in France by the Loi Evin. In 2016 the Danish brewer Carlsberg sponsored the UEFA Euro 2016 finals, held in France, and used the alibis ‘Probably’ and ‘…the best in the world’ in place of Carlsberg in pitch-side advertising. We have quantified the advertising exposure achieved during the final seven games in the UEFA Euro 2016 championship.